A ciência da religião na Torre de Marfim? uma análise sobre a significância da área, do ponto de vista de mestres e doutores formados na PUCSP - Costa, Gilmar Gonçalves da (2012)
In which professional context are the alumni, the masters and the PhDs, with a Religious Studies degree at Pontifícia Universidade Católica de São Paulo, acting? Are these Religious Studies professionals working in the field or in other branches of scholarship, such as Geography, History, Sociology, Psychology, Pedagogy, Philosophy, Theology or yet, in the commercial and industrial sectors? The present research aims at answering these questions. For that, it was based upon interviews and questionnaires with nearly 70 questions related to the professional function of a Religious Studies degree, between the years of 2009 and 2011. From the reading of the data, in light of theoretical approaches, the categories used were work market and Religious Studies. The data show that, out of the 75.5% of those with a masters degree, 16% work neither in the field of Religious Studies nor in the field of Education.; 31% correspond to those that aren t working in their field Religious Studies but dedicate themselves either to the field of Education or to the field of Research; 36% work exclusively with Religious Studies. Meanwhile, out of the 24.5% of those with a PhD degree in Religious Studies, 74% work in the field of Education and 26% of them, with Psychology. Of the total sample, 33% act as autonomous professionals, without the establishment of a formal work relationship; 33% in the private sector, 21% as small business managers or owners and 13% in the public sector. According to them, the reason why this is so is the lack of options and opportunities in the work market. Others highlight the fact that they do not work in the area because they understand it is not possible to conciliate research and studying. One hopes that this research has contributed to clarifying some of the fake antinomies used in relation to Religious Studies